Modern approaches in the treatment of patients with Paget-Schretter syndrome - I. N. Sonkin; L. I. Syromyatnikova; E. Kh. Alieva; S. A. Mehryakov (Евразийский Кардиологический Журнал)
Goal. Consider the management of patients with effort thrombosis (Paget-Schretter syndrome).The article presents the modern vision of the problem of effort thrombosis. This review is aimed at describing the epidemiology, pathophysiology, diagnosis and treatment of patients with Paget-Schretter syndrome. SPS occurs spontaneously, as a rule, in young, healthy and active patients aged 20-30 years after strenuous physical activity. The ratio of men and women is 2:1, recently there has been a growing trend among women. The main complaints of patients with SPS include swelling of the affected limb, discomfort when moving the affected arm, pain and heaviness when trying to raise the arm up. When examining these patients, attention is paid to hyperemia of the skin or their cyanotic nature, pasty limbs, as well as an enhanced venous pattern on the shoulder, the so-called Arshel sign. The diagnosis is based on the data of anamnesis, physical examination, the “gold standard of diagnostics” – ultrasound examination of veins, the sensitivity and specificity of which is 70-100%. The first step in the diagnosis can be the evaluation of the D-dimer, with its negative values, the SPSH is rejected. With an obvious clinic and controversial results of serial ultrasound examinations, other imaging methods are used, such as computed contrast tomography, magnetic resonance imaging, the diagnostic value of which is especially significant in occlusive venous thrombosis.SPS differs not only from DVT of the lower extremities, but also from secondary DVT of the upper extremities, which determines the peculiarities of management of this category of patients, including surgical treatment aimed at preventing subclavian vein compression in the future. The article summarizes the experience in the management of patients with blood thrombosis.